Anapidae (Arachnida: Araneae), a spider family newly recorded from Laos - Lin, Yucheng; Li, Shuqiang; Jäger, Peter (Zootaxa, 2013)
The spider family Anapidae is reported from Laos for the first time. One new species is described: Pseudanapis namkhan n. sp. from Nam Khan Valley, Luang Prabang Province. Another species is recorded for the first time from Champasak Province, Laos and the following new synonymy is proposed: Sinanapis thaleri Ono 2009 = Sinanapis crassitarsus Wunderlich & Song 1995 n. syn. Morphological descriptions, diagnoses and comparative illustrations are provided for the two species.